Efficacy of oral erythromycin to enhance feeding tolerance in preterm infants - Made Sukmawati; Rinawati Rohsiswatmo; Rulina Suradi; Pramita Gayatri (Indonesian Pediatric Society, 2017)
Background Feeding intolerance is a common condition that affects preterm infants. Erythromycin is a prokinetic agent used to treat feeding intolerance, but its efficacy remains inconclusive.Objective To evaluate the effectiveness of oral erythromycin to enhance feeding tolerance in preterm infants.Methods This prospective, randomized controlled trial in preterm infants was conducted at Sanglah Hospital, Denpasar, Bali, from June 2015 to January 2016. Eligible infants were randomized to receive either 12.5 mg/kg/dose oral erythromycin or a placebo, every 8 hours. The primary outcome was the time to establish full enteral feeding. The secondary outcomes were body weight at full enteral feeding and length of hospital stay.Results Of 62 initial subjects, 3 infants dropped out of the study. Thirty infants were given erythromycin and 29 infants were given placebo. The baseline characteristics of the two groups were similar, with mean of gestational ages of 31.4 (SD 1.7) weeks in the erythromycin group and 32.4 (SD 2.2) weeks in the placebo group. The median times to reach full enteral feeding did not significantly differ between the two groups, with 10 (SD 5.3) days in the erythromycin group vs. 8 (SD 6.5) days in the placebo group (P=0.345). Also, median body weights at full enteral feeding and lengths of hospital stay were not significantly different between the two groups.Conclusion Erythromycin of 12.5 mg/kg/dose every 8 hours as prophylactic treatment does not significantly enhance feeding tolerance in preterm infants. Median body weights at full enteral feeding and length of hospital stay are not significantly different between the erythromycin and placebo groups.